Document Design of Quality Management System Using Cloud Computing at PT XYZ - Adiyasa, Farid Dwi; Andajani, Erna (Eduvest - Journal of Universal Studies, 2025)
In the era of Industry 4.0, the integration of advanced technologies in quality management has become a necessity to enhance operational efficiency and data security. This study aims to design a Quality Management System (QMS) document based on ISO 9001:2015 for PT. XYZ by leveraging cloud computing as a Quality 4.0 technology. The research addresses the company's need for secure, centralized document storage and timely information dissemination to external stakeholders. A digital application, in the form of a website, was developed using the waterfall model, which allows for a systematic and structured software development process. This website is integrated with Google Cloud Storage to facilitate secure and scalable document management. The findings indicate that the QMS documentation system designed using cloud computing effectively aligns with the operational requirements of PT. XYZ and provides practical benefits in terms of accessibility, efficiency, and risk mitigation related to document loss. The implementation of this system demonstrates the feasibility and advantage of adopting digital solutions for quality management documentation. This research contributes to the digital transformation of quality systems in manufacturing and service industries, offering a reference model for organizations seeking to modernize their quality documentation processes.